PERAN BADKO DALAM PENINGKATAN KUALITAS SDM PENGAJAR TPQ KECAMATAN SAWIT KABUPATEN BOYOLALI - Dwi Ade Juhdi (Program Studi Manajemen Dakwah, FUAD, IAIN Pontianak, 2022)
The purpose of the study was to determine, describe and analyze the role of BADKO administrators in improving the quality of TPQ teaching human resources in Sawit District. The formation of TPQ teachers with quality human resources, one of which is inseparable from the role of the BADKO management in organizing various activities related to improving the quality of TPQ teaching human resources. The type of research used in this research is qualitative research. The results of this study the authors can conclude that: 1) BADKO Sawit Management Conducts periodic guidance to TPQ teachers and the surrounding community related to the movement to complete the Al-Qur'an illiteracy. 2) Conduct managerial training in TPQ management to TPQ teachers in Sawit District. 3) Create a TPQ teaching curriculum. 4) Conduct various trainings ranging from training on how to teach to entrepreneurship training and so on. 5) Hold activities that can foster friendship between TPQ teachers. 6) Distributing various aid information from the Government or other institutions to each TPQ.